ANALISIS SENGKETA ZONA EKONOMI EKSLUSIF ANTARA INDONESIA DAN RRT DI KEPULAUAN NATUNA - Kalembang, Joseph Victoryadi; -, Yuwanto - (Journal of Politic and Government Studies, 2020)
The nine dash line claim made unilaterally by the PRC in the South China Sea intersects with the Exclusive Economic Zone area in the northern sea of the Natuna Islands. This raises various problems not only for the two countries, but also with other ASEAN countries. Supervision of the territory is very necessary for Indonesia in maintaining the unity and integrity of the Unitary Republic of Indonesia, therefore it is necessary to have a relevant policy to maintain the sovereignty of the region. This study aims to determine the development of Indonesian national law in terms of policy making and the Government's efforts to maintain its regional sovereignty. The results showed that the efforts made by the Government in taking action to maintain the sovereignty of the Exclusive Economic Zone in the northern sea of the Natuna Islands were to use international instruments, bilateral instruments, National Legislation, and technical approaches based on A Manual on Technical Aspects of UNCLOS 1982 (TALOS) as a guideline in realizing UNCLOS 1982. Implementation of Indonesia's policy in maintaining its territorial sovereignty includes: infrastructure development, safeguarding and managing marine resources, as well as maritime cooperation with investor countries in order to gain recognition that the Natuna region belongs to Indonesia.